Penerapan Etika Bisnis Islam Untuk Meningkatkan Kualitas Kinerja Karyawan Perusahaan pada CV abdi Makmur Surabaya - Riananda, Rias Mei; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2021)
This study aims to provide information related to the application of Islamic business ethics in a company to improve the quality of performance in that company. This study was written using a descriptive qualitative approach to determine the Islamic view of the application of business ethics and to know the concept of the application of Islamic business ethics in improving the quality of company employee performance. The object taken in this study is CV Abdi Makmur, which is a company engaged in services and trade with the address Jl. Margorejo number 26 Surabaya. The data used in this study are primary data obtained from interviews with company leaders, employee representatives, and consumer representatives with data validity testing using source triangulation and data collection techniques in the form of interviews, observations, and documentation. The results obtained from this study are that the company CV Abdi Makmur has implemented the principles of Islamic business ethics in all company activities that have an impact on the quality of the performance of qualified employees because they are able to meet the performance appraisal criteria for qualified employees.